(untitled) (Proceedings of Southern Federal University. Philology, 2014)
The authors examine teaching writing competency in foreign language at linguistic University level from the point of view of theory, found in educational standards and methodological recommendations, as well as pedagogical practice. The analysis shows, that there is a tendency of making written speech study an equal part of educational process. Nevertheless higher education still lacks an integral approach of writing competency development, together with language level requirements. Secondary school experience of Unified State Exam (USE) may serve as a benchmark in this matter. Keywords: writing competency, educational standards, methodological recommendations, pedagogical practice, higher education Authors: Vertogradova L.A., Volovikova M.L.